2014
DOI: 10.1097/rhu.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fatigue in Rheumatoid Arthritis (by Functional Assessment of Chronic Illness Therapy–Fatigue Score) and Its Relation to Disease Activity and Anemia

Abstract: The fatigue experienced by the patients with RA is strongly associated with the severity of disease activity and is independent of anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 9 publications
0
29
1
Order By: Relevance
“…It is also necessary to remember that fatigue can be associated with side effects of traditional disease modifying drugs, such as methotrexate and leflunomide [32]. Among women with psoriatic arthritis in our study, the fatigue significantly increased during methotrexate therapy (p = 0.037), we did not observe such a correlation among women with psoriasis, which could be caused by lower methotrexate doses applied in the treatment of skin disease (p = 0.045).…”
Section: Discussioncontrasting
confidence: 59%
“…It is also necessary to remember that fatigue can be associated with side effects of traditional disease modifying drugs, such as methotrexate and leflunomide [32]. Among women with psoriatic arthritis in our study, the fatigue significantly increased during methotrexate therapy (p = 0.037), we did not observe such a correlation among women with psoriasis, which could be caused by lower methotrexate doses applied in the treatment of skin disease (p = 0.045).…”
Section: Discussioncontrasting
confidence: 59%
“…Fatigue experienced by patients with RA can be strongly related to disease activity as assessed using DAS28 [24], and improvements in fatigue with treatment have been shown to correlate with reductions in disease activity [22]. Examination of the relationship between fatigue and disease activity in biologic-naïve patients with RA initiating TNF-inhibitor therapy found that approximately half of the effect on fatigue associated with reduction in clinical symptoms (measured by DAS28 [CRP]) was indirect, mediated through a reduction in pain [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, when assessing the content of these items, the health-related problems might also be relevant for employees with other chronic diseases. For instance, fatigue is indicated as one of the most unpleasant problems among patients with rheumatoid arthritis [27], and uncertainty about the future is also experienced by patients with multiple sclerosis (MS) [28]. Workers with a chronic health condition (e.g., musculoskeletal conditions) also experienced employment difficulties, such as reduced work ability [29].…”
Section: Discussionmentioning
confidence: 99%